The Economics of Investing in Universal Preschool Education in California - Karoly, Lynn A. (RAND Corporation, 2005)
There is increased interest in California and other states in providing universal access to publicly funded preschool education. In considering such a program, policymakers and the public focus on the potential benefits and costs of such a program. This study aims to inform such deliberations by conducting an analysis of the economic returns from investing in high-quality preschool education in the state of California.